2018
DOI: 10.1038/s41598-018-25161-w
|View full text |Cite
|
Sign up to set email alerts
|

Action-effect related motor adaptation in interactions with everyday devices

Abstract: Human action planning relies on integrated representations of motor acts and the associated consequences, which implies that changing the set of effects associated to a motor act might directly influence action planning and control. The present study investigated the hypothesis that action-effect manipulations also affected the motor components of the actions even when only a single action option was available. Participants performed simple everyday actions (pinched a plastic sheet, pressed a button, tapped on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…(Release might be also initiated if tactile stimulation reaches a certain level, even if auditory effects are not elicited, which could explain how releasing the device is induced in the motor condition.) However, based on previous studies (Horváth, Bíró, & Neszmélyi, 2018) and additional analyses of the current results (see online supplementary material) it seems likely that the tone eliciting movements used in the current study can be indeed regarded as ballistic and action-effect-related motor adaptation is mainly determined by offline mechanisms of action planning. Thus, in the following, we focus on explanations that are related to such offline processes, and the potential contribution of online control is discussed in the online supplementary material.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…(Release might be also initiated if tactile stimulation reaches a certain level, even if auditory effects are not elicited, which could explain how releasing the device is induced in the motor condition.) However, based on previous studies (Horváth, Bíró, & Neszmélyi, 2018) and additional analyses of the current results (see online supplementary material) it seems likely that the tone eliciting movements used in the current study can be indeed regarded as ballistic and action-effect-related motor adaptation is mainly determined by offline mechanisms of action planning. Thus, in the following, we focus on explanations that are related to such offline processes, and the potential contribution of online control is discussed in the online supplementary material.…”
Section: Discussionmentioning
confidence: 68%
“…It is important to note that the task in Experiment 3 (constant interval production) differed from those in Experiment 1 and 2 (random interval production). Action-effect-related motor adaptation has been observed previously with both of these tasks (Horváth et al, 2018; Neszmélyi & Horváth, 2017), but we are unaware of any studies investigating potential task-related differences. Currently no results indicate that tendencies observed in any of the three experiments would be specific to the respective task.…”
Section: Methodsmentioning
confidence: 90%
“…The present design does not rule out potential alternative explanations, however, so that several theoretical possibilities might also account for the benefits from action effects with more features: First, several studies have demonstrated that when actions (e.g., pinches, button presses, tapping on a table) elicit a more reliable, higher quality feedback, action control is more effective (Neszmélyi & Horváth, 2017, 2018. In our study, the action effects in the audiovisual group might provide more reliable feedback than in other groups, allowing for more efficient motor control (Horváth, Bíró, & Neszmélyi, 2018). Thus, participants in the audiovisual group might be more confident in the success of the actions and can execute not only the subsequent actions within the motor sequence but also all subsequent sequences at a higher speed.…”
Section: Discussionmentioning
confidence: 74%
“…Kunde et al (2004) suggested that a similar compensatory averaging process affects the force exerted during action execution: if an agent aims at producing a constant mean intensity, a quiet tone effect calls for a higher intensity of action (i.e., higher peak force [PF]) as a loud tone effect (i.e., lower PF). 1 In a similar vein, Horváth et al (2018) found that the PF produced during tapping was attenuated by the presence of an auditory effect compared with situations without additional effects.…”
Section: Introductionmentioning
confidence: 88%